Vibration-based structural health monitoring of a RC-masonry tower equipped with non-conventional TMD. (1st December 2020) - Tronci, E.M.; De Angelis, M.; Betti, R.; Altomare, V.
Highlights: First monitoring system on a historic structure equipped with a Non-Conventional Tuned TMD. Three-years monitoring on structure featuring an isolation. The temperature has daily and seasonally effect on the structural parameters. Natural frequencies are affected by changes in the masonry microcracks configuration. Results obtained from the application of an automated OMA methodology are presented. Abstract: This article presents the development and the results of three years of implementation of an automated vibration-based structural health monitoring system for modal tracking the dynamic characteristics of a concrete-masonry Civic Tower in Rieti (Italy) equipped with a passive vibration control system, a Non-Conventional Tuned Mass Damper. The system is based on the data recorded by a small number of high-sensitivity accelerometers set on remote automated modal parameters tracking. The analysis of monitoring data highlights the main characteristics of the response of the tower to operational vibrations and low-return period earthquakes. Despite the low levels of vibration in operational conditions, the system can track the evolution of the structural frequencies along time and successfully capture their dependence from temperature, both daily and seasonally. Moreover, the robustness of the modal identification procedure allowed the detection of anomalous variation from the validated reference dynamics of the structure.